Documento como obra: contribuições para a organização da informação - Marcelo Nair dos Santos (2013)
This study deals with document as work in Information Organization on processes related to documents cataloging and arrangement. Information Organization is the area of Information Science which includes the fundamentals and methods for production and management of documentary information systems. Such fundamentals and methods are used on processes for that area. Among them, we highlight the documents cataloging and arrangement where the notion of work is more effective. Thus, this study aims to explore the document as work in Information Organization, seeking to contribute to the construction of these concepts (as document, work and item) in Information Science, in order to: advance our formulation about the fundamentals concepts to the processes for the area which involve the notion of the work; offer productive alternatives to the terminological variation around the object from which Information Organization works on; discuss the processes and products involving the notion of work in Information Organization in order to provide a conceptual framework, for facilitating concrete operations; and promote the advancement in Information Science from the contributions of Science Library and Documentation, regarding the subject of this work. This research is carried out in an exploratory qualitative approach and it uses bibliographic research as methodological procedure. In this way, there are two parts: on the first, we explore fundamental aspects of the work that deals with its creation, materialization, and reception, including the concepts of the notion of document and documentary unit; on the second part, we discuss procedural aspects of the work on the bibliographic record, conceptual models, normative tools of cataloging, and documents arrangement. On cataloging, the analyses indicate that the integrated notions of document, documentary unit, and work are a viable way for the fundamental processes for preparing bibliographical records in the database.